CONTENT CREATORS AND VIEWERS PERCEPTIONS OF THE TIKTOK ALGORITHM - Rita Gistalia; Adeline Rara Wiratama; Andri Wahyuni; Tan Evan Tandiyono (Jurnal Manajemen Perbankan Keuangan Nitro, 2026)
The development of digital technology has significantly transformed information consumption patterns and social media behavior, particularly among Generation Z. One of the most influential platforms is TikTok, which utilizes algorithmic systems to deliver content through the For You Page (FYP). This algorithm indirectly shapes users habits, attention, and time management. This study aims to analyze the perceptions of content creators and viewers toward the TikTok algorithm and its impact on Generation Z time management ability. This research employs a descriptive qualitative approach involving two Generation Z participants, consisting of one content creator and one viewer from Universitas 17 Agustus 1945 Surabaya. Data were collected through in-depth interviews and documentation of TikTok usage activities over one week. The data were analyzed qualitatively through data reduction, data presentation, and conclusion drawing. The findings indicate that the TikTok algorithm significantly influences Generation Z time usage behavior. While the algorithm enhances user engagement, it also reduces self-control over time, leading to excessive content consumption. However, some participants have begun to develop time management strategies, such as limiting usage duration and selectively engaging with content, in order to maintain productivity. This study highlights the importance of digital literacy and user awareness in responding to social media algorithms to promote healthier and more productive technology use